2013
DOI: 10.1080/09658211.2012.756040
|View full text |Cite
|
Sign up to set email alerts
|

Remembering President Barack Obama's inauguration and the landing of US Airways Flight 1549: A comparison of the predictors of autobiographical and event memory

Abstract: We examined and compared the predictors of autobiographical memory (AM) consistency and event memory accuracy across two publicly documented yet disparate public events: the inauguration of Barack Obama as the 44 th President of the United States on January 20 th , and the emergency landing of US Airways Flight 1549, off the coast of Manhattan, on January 15 th . We tracked autobiographical and event memories for both events, with assessments taking place within two-and-a-half weeks of both events (Survey 1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…This finding is consistent with the beneficial effect of repetition demonstrated in other studies assessing semantic memory in young adults [40,41] and aMCI [28]. This result is also similar to results reported by Müller et al in aMCI and AD patients which showed that better performance was associated with greater self-reported retrieval frequency of historic events [20].…”
Section: Public Events Memory 16supporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with the beneficial effect of repetition demonstrated in other studies assessing semantic memory in young adults [40,41] and aMCI [28]. This result is also similar to results reported by Müller et al in aMCI and AD patients which showed that better performance was associated with greater self-reported retrieval frequency of historic events [20].…”
Section: Public Events Memory 16supporting
confidence: 82%
“…Indeed, beneficial effects of repetition on consolidation processes have been found in some studies assessing memory for public events in healthy subjects. For example, Koppel and colleagues showed a positive relationship between the accuracy of memories concerning the emergency landing of US Airways Flight 1549 off the coast of Manhattan in 2009 and the frequency with which participants reported having thought or spoken, as well as watched, read and listened to the media coverage about this event [40]. In another study, prior retrieval caused by repeated testing seemed to promote better recall for September 11 th 2001 events [41].…”
Section: Introductionmentioning
confidence: 97%
“…This speaks against the possibility of the Living-in-History effect being a product of the reminiscence bump. Future studies with adults who have not lived through World War II but who experienced the fall of the Berlin Wall or other positively perceived public events like president Obama's inauguration (Koppel, Brown, Stone, Coman, & Hirst, 2013) could clarify whether a positive public event can lead to at least a moderate Living-in-History effect.…”
Section: Discussionmentioning
confidence: 99%
“…Others have argued, however, that these memories are characterized by unusual vividness, subjective certainty, and longevity, if not accuracy (e.g., Talarico & Rubin, 2007). Because of these characteristics, flashbulb memory continues to be a topic of strong interest to both memory researchers and the public (e.g., Day & Ross, in press; Hirst et al, 2009; Koppel, Brown, Stone, Coman, & Hirst, 2013; Kraha & Boals, in press). …”
Section: Autobiographical Memory and Emotion: The Concept Of Flashbulmentioning
confidence: 99%